Future of External Reporting. Issue 166 (January 2016) - Powers, Kristina
Abstract : This chapter builds on prior chapters and focuses on higher education trends on the horizon and the resulting impact on external reporting for institutional researchers. Three practical recommendations and examples for institutional researchers are also presented.